Extended Kalman filter for fouling detection in thermal power plant reheater. (April 2018) - Sivathanu, Anitha Kumari; Subramanian, Srinivasan
Abstract: A model based on-line foul monitoring approach for a power plant reheater is proposed. Dual Extended Kalman Filter (DEKF) is designed to estimate the model parameters that influence fouling. Based on the estimated parameters the performance index (Cleanliness Factor) is obtained to retrieve the extent of fouling on reheater. The simulation and experimental validation using power plant data shows the efficacy of DEKF over conventional Joint-EKF (JEKF) in estimating the model parameters. The outcome of the work will assist in soot blow scheduling for reheater by perceiving the fall in cleanliness factor and will also help in analysing its impact on heat transfer efficiency. Highlights: Mathematical model of reheater is simulated and validated using experimental data. Dual and Joint Extended Kalman filter is deployed to estimate states and parameters of the reheater model. Effect of ash fouling on flue gas and steam output temperatures is analysed. Drift in parameters with effect of fouling is detected using cumulative sum change detection technique. Cleanliness Factor of reheater is obtained to infer the extent of ash fouling.